Seminar Evaluasi Manajemen Pengelolaan Lingkungan Belajar Di Satuan Paud Se-Kecamatan Ulu Musi Kabupaten Empat Lawang - Haryono, Mimpira; Bendriyanti, Rita Prima; Ruslini, Dwi (Jurnal Karya Nyata Pengabdian, 2025)
This community service activity aims to improve the understanding and skills of PAUD teachers throughout Ulu Musi District, Empat Lawang Regency, in evaluating the management of learning environment management. An optimal learning environment plays a very important role in supporting the holistic growth and development of early childhood. However, the results of initial observations showed that most teachers still have limited understanding and rarely conduct structured evaluations. This activity was carried out through a participatory seminar method and direct training involving 30 teachers from various PAUD units. The results of the activity showed a significant increase in teacher knowledge, the ability to use simple evaluation instruments, and the emergence of initiatives to prepare follow-up plans (RTL) in each PAUD unit. This seminar also succeeded in identifying major challenges, such as limited facilities and lack of collaboration with external parties, and offered applicable solutions that can be applied according to the local context. Thus, this activity makes a real contribution to strengthening the capacity of teachers in managing a safe, comfortable learning environment that supports the development of early childhood.